Identification of sequence polymorphisms in the mitochondrial deoxyribonucleic acid displacement-loop region as risk factors for systemic lupus erythematosus - Ruixue Lai; Xiaoyun Zhang; Kuangyuan Qiao; Xueqing Gao; Shang Li; Ruixing Zhang; Yixin Qi; Chenxing Peng (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate the relationship between sequence polymorphisms (SNPs) in the displacement-loop (D-loop) region of mitochondrial deoxyribonucleic acid (mtDNA) and systemic lupus erythematosus (SLE) in Chinese female patients. Patients and methods: This cross-sectional study was conducted between May 2017 and October 2017. The mtDNA was extracted from the peripheral blood of 97 female SLE patients (mean age 40.8 years; range, 20 to 79 years) and 108 age-matched healthy controls (mean age 48.7 years; range, 22 to 78 years). The SNPs of mtDNA D-loop were verified by polymerase chain reaction amplification and sequence analysis. The allele frequencies of D-loop region were compared by the Chi-square test between SLE and control groups. Results: The SNP accumulation in SLE patients was significantly higher than that in the controls (p=0.027, 95% confidence interval [CI]: 0.075, 1.210). The frequencies of the major alleles of the nucleotides 73G/A (p<0.001, odds ratio [OR]=1.241) and 195T/C (p=0.047, OR=4.318) as well as the minor allele of nucleotide 199T/C (p=0.048, OR=0.279) were significantly higher in the SLE patients than in the controls, which indicated that 73G, 195T and 199C allele in the D-loop of mtDNA were associated with the risk of SLE. Further analysis indicated that the reactive oxygen species level in the SLE patients was significantly higher than that of controls (mean fluorescence intensity ± standard deviation: 3054.333±256.099 vs. 2099.167±599.662, p=0.009, 95% CI: 321.243, 1589.091). Conclusion: This study indicated the SNPs in the mtDNA may associated with the risk of SLE. Analysis of SNPs in the mitochondrial D-loop may help identify individuals who are at high risk of developing SLE.